2007
DOI: 10.1584/jpestics.g06-35
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of Trichoderma asperellum SKT-1, a biocontrol agent against Gibberella fujikuroi

Abstract: Trichoderma asperellum SKT-1 and Gibberella fujikuroi, known as causal agents of "Bakanae" disease, were both transformed with genes encoding green fluorescent protein (GFP) and hygromycin B (hygB) by restriction enzyme-mediated integration (REMI). Rice seeds inoculated with GFP-tagged G. fujikuroi showed "Bakanae" symptoms. GFP-tagged SKT-1 maintained biocontrol activity against the pathogen by soaking seeds in SKT-1 spore suspension. Then, we monitored in situ interactions between SKT-1 and G. fujikuroi on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…KNB-422 might sense some biological materials such as secondary metabolites from G. fujikuroi hyphae and grow toward the pathogen. Watanabe et al (2007) reported that co-culture of Trichoderma asperellum SKT-1, another biocontrol agent against Bakanae disease, with G. fujikuroi on PDA resulted in loss of GFP fluorescence in G. fujikuroi hyphae. Trichoderma asperellum acts parasitically toward the pathogen colonizing the mutual regions in rice seed embryos.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…KNB-422 might sense some biological materials such as secondary metabolites from G. fujikuroi hyphae and grow toward the pathogen. Watanabe et al (2007) reported that co-culture of Trichoderma asperellum SKT-1, another biocontrol agent against Bakanae disease, with G. fujikuroi on PDA resulted in loss of GFP fluorescence in G. fujikuroi hyphae. Trichoderma asperellum acts parasitically toward the pathogen colonizing the mutual regions in rice seed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pMK412 (Watanabe et al 2007) carried a GFP gene (egfp) driven by the translation elongation factor (TEF) promoter from Aureobasidium pullulans and the glucoamylase (gla) terminator from Aspergillus awamori, and the hygromycin B phosphotransferase gene (hph) under control of trifunctional polypeptide (trpC) promoter and terminator from Aspergillus nidulans. Plasmid pDsRed2 (Takara Bio, Ohtsu, Japan) carried dsred2.…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ptef was amplified from pMK412 24) with the Ptef-F and Ptef-R primers. Ptef fragment (0.8 kb) was digested by EcoRV and ligated with EcoRV and HindIII digested pCSN43 blunted by the Klenow fragment of Escherichia coli DNA polymeraseI.…”
Section: Methodsmentioning
confidence: 99%